Single-cell characterization of in vitro migration and interaction dynamics of T cells expanded with IL-2 and IL-7 - Tauriainen, Johanna M.; Gustafsson, Karin; Göthlin, Mårten; Gertow, Jens; Buggert, Marcus; Frisk, Thomas W.; Karlsson, Annika C.; Uhlin, Michael; Önfelt, Björn (Frontiers in Immunology, 2015)
T cells are pivotal in the immune defense against cancers and infectious agents. To mount an effector response against cancer cells, T cells need to migrate to the cancer-site, engage in contacts with cancer cells and perform their effector functions. Adoptive T cell therapy is an effective strategy as treatment of complications such as relapse or opportunistic infections after hematopoietic stem cell transplantations. This requires a sufficient amount of cells that are able to expand and respond to tumor or viral antigens. The cytokines interleukin (IL)-2 and IL-7 drive T cell differentiation, proliferation and survival and are commonly used to expand T cells ex vivo. Here, we have used microchip-based live-cell imaging to follow the migration of individual T cells, their interactions with allogeneic monocytes, cell division and apoptosis for extended periods of time; something that cannot be achieved by commonly used methods. Our data indicate that cells grown in IL-7 + IL-2 had similar migration and contact dynamics as cells grown in IL-2 alone. However, the addition of IL-7 decreased cell death creating a more viable cell population, which should be beneficial when preparing cells for immunotherapy.